Progressive Myoclonic Epilepsy’-like presentation of Cerebrotendinous Xanthomatosis in an Indian Family with A Novel C.646+1G>A Splice Site Mutation - Desai, Karan M. (Epilepsy Behav Rep, 2020)
Cerebrotendinous Xanthomatosis (CTX) is a rare autosomal-recessive inborn disorder of bile acid metabolism due to mutations in the CYP27A1 gene. It presents with a diverse range of neurological and non-neurological symptoms. We present a case of CTX with a progressive myoclonic epilepsy (PME) like phenotype and a family history of CTX. The proband had a generalized epilepsy with prominent myoclonus. He also had intellectual decline, ataxia, bipyramidal dysfunction and peripheral neuropathy. The younger sibling had a milder generalized epilepsy without myoclonus along with behavioral issues, ataxia, neuropathy, and prominent tendon xanthomas. Both the siblings had developmental cataracts. MRI Brain of both had dentate hyperintensities with cerebellar atrophy. The proband’s EEG showed severe background slowing with multifocal interictal discharges. Targeted gene of analysis proband revealed a novel homozygous 5′ splice site variation in intron 3 of the CYP27A1 gene. We present a novel phenotype and genotype of CTX presenting with a syndrome of myoclonic epilepsy. This is the first PME-like presentation of CTX to the best of our knowledge. CTX may present with a PME-like clinical phenotype and should be considered as a treatable cause within the differential diagnostic evluation of syndromic epilepsies involving an atypical familial myoclonic epilepsy.